The Oxford handbook of environmental criminology - Bruinsma, Gerben; Johnson, Shane D., 1971- (New York, NY : Oxford University Press, 2018)
The study of how the environment, local geography, and physical locations influence crime has a long history that stretches across a number of research traditions. These include the neighborhood-effects approach developed by the Chicago school of sociology in the 1920s; modern environmental criminology that explains the geographic distribution of crime; the criminology of place, which focuses on crime rates at specific places over time; and a newer approach that attends to the perception of crime and disorder in communities. Aided by new mobile and digital technologies as well as improved data reporting in recent decades, research in environmental criminology has developed at a rapid pace within each of these approaches. Despite these advances, research in the subfield of environmental criminology remains fragmented, and competing theories are often kept apart.
Social Spatial Influences / Pamela Wilcox, Kristin Swartz -- Testing Theories of Social Disorganization in Nigeria / Faisal Umar, Shane D. Johnson, James A. Cheshire -- Signal Crimes: How the Harms of Crime and Disorder Travel across Social Space-Time / Martin Innes, Helen Innes -- Egohoods: Capturing Change in Spatial Crime Patterns / John R. Hipp, Christopher J. Bates -- The Criminology of Places / Cody W. Telep, David Weisburd -- Built Environment, Land Use and Crime / Kathryn Wuschke, J. Bryan Kinney -- Street Networks and Crime / Toby Davies, Kate J. Bowers -- Macro Level Generators and Crime (Parks, Stadiums, and Transit Stations) / Andrew Newton -- Mobility and Location Choice of Offenders / Wim Bernasco -- Crime Concentrations: Hot Dots, Hot Spots and Hot Flushes / Dainis Ignatans, Ken Pease -- Time and Opportunity / Lisa Tompson, Timothy Coupe -- How Do We Get to Causal Clarity on Physical Environment-Crime Dynamics? / Ralph B. Taylor -- Studying Situational Effects of Setting Characteristics: Examples from the Study of Peers, Activities and Neighbourhoods / Frank M. Weerman, Evelien Hoeben, Wim Bernasco, Lieven J. R. Pauwels, Gerben J.N. Bruinsma -- Guardianship / Danielle M. Reynald -- Place Management / John E. Eck, Tamara D. Madensen -- Victimization Surveys in Environmental Criminology / Andromachi Tseloni, Nick Tilley, Graham Farrell -- Organized Crime and Places / Edward R. Kleemans -- (Juvenile) Gangs and Space / Matthew Valasik, George Tita -- Riots, Space and Place / Peter Baudains, Shane D. Johnson -- Maritime Piracy / Michael Townsley -- Geoprofiling Terrorism / Kim Rossmo -- Child Sexual Abuse and Opportunity / Richard Wortley -- The Individual Perspective / Lucia Summers, Rob T. Guerette -- Does Crime Impact Real Estate Prices? An Assessment of Accessibility and Location / Vania Ceccato, Mats Wilhelmsson -- What have we Learned from Environmental Criminology for the Prevention of Crime? / Brandon C. Welsh, Sema A. Taheri -- Deciding on the 'Appropriate' Unit of Analysis: Practical Considerations in Environmental Criminology / Brian Lawton -- GIS and Spatial Analysis / Martin Andresen -- Systematic Observation / Ian Brunton-Smith -- The Role of Innovative Data Collection Methods in Advancing Criminological Understanding / Reka Solymosi, Kate J. Bowers -- Computer Simulations. Agent-Based Environmental Criminology / Daniel Birks -- New Steps in Visualization for Research in Environmental Criminology / Patricia L. Brantingham, Paul J. Brantingham, Justin Song, Valerie Spicer -- Environmental Criminology: History, Scope and State of the Art / Gerben J.N. Bruinsma, Shane D. Johnson -- Cybercrime and Place: Applying Environmental Criminology to Crimes in Cyberspace / t
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 30, 2018).
Keywords: Offenses against the environment; Criminology